Predictors of depressive symptoms and effective coping strategies among open and distance learning nursing students - Joel Olayiwola Faronbi; Anifat Taiwo Adebiyi; Augustine Olarewaju Idowu; Grace Oluwatoyin Faronbi; Omolola Oladunni Irinoye (Elsevier, 2021)
Background: Depression is a challenge of public concern with high disability adjusted life years (DALY). Increasing prevalence of depression and suicide among youths demand urgent attention especially among every cohort of youths who may face increasingly challenging situations. Open and distance learning nursing students combine family and work roles with the demanding teaching-learning activities of the (ODL) programme in Obafemi Awolowo University. This study was conducted to assess possible depressive symptoms and coping strategies among Open and Distance Learning (ODL) Nursing Students of Obafemi Awolowo University, Ile-Ife, Nigeria with the intention of taking actions to mitigate the challenges. Methodology: A cross-sectional study was conducted among 272 ODL nursing students and quantitative data were collected using Beck's Depression Inventory and Carver Coping Inventory. Pearson Chi-square and regression analysis were conducted to examine the association between depressive symptoms and predict effective coping among the students. Results: Majority of the respondents (63.6%) had mild depression. The most used coping strategies include suppression of competing activities 67.5% (11.29 ± 3.69), religious coping 57.4% (11.27 ± 3.98), and planning 59.2% (11.19 ± 3.83). Depressive symptoms were associated with religious coping (p < 0.05), mental disengagement (p = 0.029), humour (p = 0.012), behavioural disengagement, restraint (p = 0.002), use of emotional social support (p = 0.006), and planning (p = 0.034). However, depressive symptom was only predicted by marital status (Β = 11.42, p < 0.001). Predictors of effective coping strategies against depressive symptoms include marital status (Β = 10.1, p < 0.001), use of emotional social support (Β = 0.97, p = 0.001), acceptance (Β = −1.13, p = 0.004), positive reinterpretation and growth (Β = −0.79, p = 0.01) and behavioural disengagement (Β = −0.80, p = 0.034). Conclusion: This study concluded that majority of ODL students experienced mild to moderate depressive symptoms but a few experienced high depressive symptoms and marriage was a predictive factor for depression. Diverse coping strategies were adopted, some were effective and some others were not. Predictors of effective coping strategies included being married, use of emotional social support, acceptance positive reinterpretation and growth and behavioural disengagement.